Determining the appropriate capital level for Farm Credit Mid-America - Perry, Nathan W. (Kansas State University, 2013)
Farm Credit Mid-America is experiencing strong growth due to the success of the farming sector in our four state territory of Tennessee, Kentucky, Indiana, and Ohio. The company is well positioned to meet the financial demands of its customers and they have an aggressive growth plan to increase total assets from $18 billion to $25 billion in five years. They also plan to add 600 new employees in that time period. Determining the appropriate level of capital to sustain growth and meet the demands of its customers will be a primary objective of the organization over the next five years. Permanent capital is viewed as a percentage of total assets at Farm Credit Mid-America with the ideal amount between 14% and 16%. A detailed analysis of the current capital level, regulatory requirements, and the projected future financial position of the company was completed to: · Define and understand capital as it applies to Farm Credit Mid-America; · Research the current capital levels for Farm Credit Mid-America; · Compare capital levels of Farm Credit Mid-America to capital levels of other Farm Credit Associations and other banks; · Understand Basel III Accords and how it applies to Farm Credit Mid-America’s capital requirements; · Complete sensitivity analysis with multiple scenarios applied to the current Farm Credit Mid-America loan portfolio to determine the effect certain events may have on capital levels; · Determine if Farm Credit Mid-America is appropriately capitalized based on the other objectives. When looking at the results, it is determined that current capital levels are in line with other Farm Credit associations and competitors. Also, Farm Credit Mid-America has met the Basel III guidelines for minimum capital requirements. The sensitivity analysis included a wide range of scenarios from normal growth rates to extreme loan portfolio distress and the effects those scenarios would have on permanent capital. The permanent capital ratio exceeded the minimum standard of 12% on all sensitivity analysis scenarios. Therefore, based on the objectives of this thesis Farm Credit Mid-America appears to be adequately capitalized.
Keywords: Capital; Core surplus; Basel accords; Farm credit mid-America; Permanent capital ratio; Agriculture, General (0473)